A delicate balance: how multinationals can harmonize local and global strategies. Issue 3 (9th May 2019) - Baumgartner, Marc André; Tippmann, Esther
Abstract : Purpose: Strategizing in a multinational corporation requires balancing global and local strategy. The purpose of this paper is to provide some insights into how multinational corporations succeed in this endeavor. Design/methodology/approach: The authors conducted a detailed qualitative investigation of the strategy-development processes at Gamma – a European multinational corporation in the materials industry. Specifically, the authors investigated strategy development in the DACH region (i.e., for the German, Austrian and Swiss subsidiaries). To collect data, they conducted interviews with key informants at the corporate headquarters and the subsidiaries and collected archival data. Findings: The data revealed that Gamma had found an approach to strategy development that balanced its global strategy with local conditions, finding a suitable way to align its global and local strategies. The authors therefore unravel three key insights revolving around subsidiaries' unique interpretations of the basic idea of global strategy, idiosyncratic strategy development processes in subsidiaries and globally and locally synchronized temporal structures. Originality/value: Knowing how to balance the strategic needs of headquarters and subsidiaries allows multinational corporations to follow a general strategy while simultaneously developing a local market strategy responsive to the individual market requirements.